Gulliver's travels - a voyage to lilliput - Swift, Jonathan (Oxford Univ Press Place of publication not identified, 2005)
Gulliver's ship is lost in a storm, and he has to swim to save his life. After many hours, he reaches land. He lies down on the shore, and falls asleep. When he wakes up, he can't get up. He is tied to the ground. His hair is tied down too, he can't move his head. He feels something walking along his body. There, standing on his chest, is a man.